Dilud: A Mobile Application to Reinforce Rote Learning in Elementary School Children with Attention Deficit Hyperactivity Disorder - Celis, Gianella (2023)
Attention and hyperactivity disorder is one of the most frequent chronic conditions in children, which generates impulsive behaviors that cause them not to be able to concentrate since they do not remember the activities in-dicated to them and, as a result, they are underperforming in school. And it is even more difficult for them since the pandemic because they must pay atten-tion to a laptop for their classes. This study aims to develop and validate if a mobile application (Dilud) allows reinforcing the working memory (WM) of primary school children from 6 to 12 years old through 4 interactive and dy-namic games that use gamification and the training method Tajima Cognitive Test (TCT). To evaluate Dilud, the authors conducted a case study using the “simple random” method, with a 6-year-old child using the WISC-V exam. The case study results show that Dilud boosts working memory (WM) by 19 points, bringing the memory level “Average Normal”. While for the usability evalua-tion, 15 children and their parents rated the usability and satisfaction with a very high score through a survey.